(untitled) (Hackensack, N.J., 2005)
This authoritative volume comprises the plenary lectures and articles by many of the field's leading researchers who were brought together for the fourth time at the congress of the International Society for Analysis, its Applications and Computation (ISAAC). A wide spectrum of topics in modern analysis is covered by the fully refereed contributions, such as complex analysis, non-linear analysis, inverse problems, wavelets, signals and images. In particular, important areas - not given special emphasis in previous meetings - include special functions and orthogonal polynomials, harmonic analysis, and partial differential equations.
Keywords: Mathematical analysis,Mathematical physics; Phân tích toán học,Vật lý toán